Antioxidant and hepatopreventive effects of Cassia angustifolia extract against carbon tetrachloride-induced hepatotoxicity in rats. (2nd November 2021) - Bellassoued, Khaled; Hamed, Houda; Ghrab, Ferdaws; Kallel, Rim; Van Pelt, Jos; Makni Ayadi, Fatma; Elfeki, Abdelfattah
Abstract: The present study aimed to investigate the preventive effects of methanol fraction from Cassia angustifolia leaf extract (MECA), associated with its phytochemical content, on CCl4 -induced hepatic toxicity in adult rats. In the controls, CCl4 induced an increase of serum biochemical parameters and triggered oxidative stress in the liver. MECA caused significant reductions in CCl4 -elevated levels of hepatic markers, total cholesterol, triglycerides, and low-density lipoprotein and increased the level of high-density lipoprotein compared to the CCl4 group. Moreover, pretreatment with the MECA produced significant reductions in lipid peroxidation (thiobarbituric acid reactive substances) and protein carbonyl level in liver tissues as compared with the untreated group. The formation of pathological hepatic lesions was strongly prevented by MECA. Overall, this study suggests that administration of MECA has a high potential to quench free radicals and alleviate CCl4 -induced hepatotoxicity in rats.